2019
DOI: 10.1002/ppap.201900060
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature plasma‐activated medium inhibited invasion and metastasis of melanoma cells via suppressing the Wnt/β‐catenin pathway

Abstract: Low‐temperature plasma (LTP) has shown promising and potential applications in the field of biomedicine. The effects of the plasma‐activated medium (PAM) inhibiting tumor cell invasion and metastasis have been verified, but the associated molecular mechanisms are poorly understood. The aim of this study was to identify the anti‐invasion and antimetastasis effects and mechanism induced by PAM on B16 melanoma cells cultured in vitro. For this purpose, an atmospheric pressure plasma jet in helium was applied to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…An important parameter in indirect CAP treatment is the interaction between the PAM and the target material (i.e., HOS cells), also called treatment time. According to the specialized literature, in previous studies different treatment times were used, starting from 10 min, up to 72 h [3,9,60,75,[77][78][79][80][81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important parameter in indirect CAP treatment is the interaction between the PAM and the target material (i.e., HOS cells), also called treatment time. According to the specialized literature, in previous studies different treatment times were used, starting from 10 min, up to 72 h [3,9,60,75,[77][78][79][80][81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…However, Mateu-Sanz et al and Liu et al were able to produce PAM without any alterations to the pH levels. The main difference in their approach was the addition of FBS to the solution that was exposed to CAP, either before or after the exposure [9,81]. According to Subramanian et al, the pH reduction observed following CAP exposure is a result of increased hydrogen ion concentration [3].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PAM has been widely studied for antitumor research, proving that its production of a large number of ROS was the main factor in cancer cell apoptosis [22,25,26]. In addition, PAM has been found to inhibit the migration of melanoma cells [27], but whether it inhibits the migration of NSCLC and its mechanisms has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…PAM can increase the level of oxidative stress in cells and thus promote or inhibit the proliferation of cells. Related studies have shown that short-term PAM treatment can promote the proliferation of fibroblasts [3], induce osteoblast differentiation [4], inhibit over 20 kinds of cancer cells cultured in vitro [5], including melanoma cells [6], prostate cancer cells [7], glioma cells [8], lymphoma cells [9], and liver cancer cells [10]. The main mechanisms of action include inducing apoptosis and necrosis of tumor cells, inhibiting proliferation signaling pathway, damaging DNA structure, and affecting migration and adhesion of tumor cells [11].…”
Section: Introductionmentioning
confidence: 99%